Healthcare workers' and parents' perceptions of measures for improving adherence to hand-hygiene - Ciofi degli Atti, Marta L (BioMed Central, 2011)
BACKGROUND: This study was conducted to evaluate perceptions of healthcare workers (HCW) and parents regarding hand-hygiene and effectiveness of measures for increasing hand-hygiene adherence, in a children's hospital in Italy. METHODS: A cross-sectional study was performed from 5 to 13 July 2010, using two self-administered anonymous questionnaires (one for HCWs and one for parents/caregivers). The questionnaires included information regarding individual perceptions associated with hand hygiene. RESULTS: We collected 139 questionnaires from HCWs and 236 questionnaires from parents. Alcohol-based handrub was reported to be available at the point of care by 95.0% of the HCWs and in the child's room by 97.0% of the parents. For both HCWs and parents, availability of alcohol-based handrub was perceived as the most useful action for improving adherence to hand hygiene (scores ≥ 6 on a 7-point Likert-type scale: 84.8% [CI95%78.0-90.1] for HCWs and 87.9% [CI95% 83.3-91.7] for parents). Parents' reminding HCWs to perform hand hygiene was perceived as the least useful action (scores ≥ 6: 48.9% [CI95% 40.5-57.3] for HCWs and 55.7% [CI95% 49.2-62.1] for parents). Factors that affected HCWs' perceptions of the effectiveness of actions for improving adherence to hand hygiene included years of practice, type of ward and previous formal training on hand hygiene. For parents, factors affecting perceptions included previous information on hand hygiene and previous hospitalizations for their child. CONCLUSIONS: Investigating HCWs' and parents' perceptions of measures for improving adherence can provide useful information for implementing actions for hand-hygiene promotion in children's hospitals. In this study, HCWs' and parents' perceptions were similar; alcohol-based hand-rub availability was perceived as the most useful tool, confirming its crucial role in multimodal interventions. Poor perception of inviting parents to remind HCWs to perform hand-hygiene has been previously observed, and deserves further investigation. Information and education activities were associated with more positive perceptions regarding various improvement measures. Though the relationship between perceptions and behaviours remains to be fully determined, HCWs should participate in formal training and families should be properly informed, not only to increase knowledge but also to improve perceptions on effectiveness of actions to be implemented.